Implementasi Core Values ASN BerAKHLAK dalam Meningkatkan Kinerja Pegawai pada Kejaksaan Negeri OKU Selatan - Nabila Shalsabila; Putra, Raniasa; Iriani, Atrika; Chairani, Annisa Larasati (Jurnal Pemerintahan dan Politik, 2025)
This study aims to determine and analyze how the implementation of core values ASN BerAKHLAK in improving employee performance at the Public Prosecutor's Office of South Ogan Komering Ulu, to know and analyze what are the inhibiting factors in the process of implementing core values ASN BerAKHLAK in improving employee performance at the Public Prosecutor's Office of South Ogan Komering Ulu. The research method was carried out with a descriptive qualitative approach to explore and analyze the implementation of core values ASN Berakhlak in improving employee performance at the South Ogan Komering Ulu State Prosecutor's Office. This research focuses on data collection through in-depth interviews with employees who are directly involved in public services at South Ogan Komering Ulu Public Prosecutor's Office.  The results of the study revealed that the implementation of the core values of a moral ASN at the South Ogan Komering Ulu Public Prosecutor's Office, which consist of service-oriented, accountable, competent, harmonious, loyal, adaptable and cooperative, is an important foundation for building an effective work culture in government agencies. These values not only improve the performance of employees, but also strengthen their commitment to public service.